2003
DOI: 10.1002/jms.504
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope labeling for matrix‐assisted laser desorption/ionization mass spectrometry and post‐source decay analysis of ribonucleic acids

Abstract: Matrix-assisted laser desorption/ionization mass spectrometry is a powerful analytical tool for the structural characterization of oligonucleotides and nucleic acids. Here we report the application of stable isotope labeling for the simplified characterization of ribonucleic acids (RNAs). An (18)O label is incorporated at the 3'-phosphate of oligoribonucleotides during the enzymatic processing of intact RNAs. As implemented, a buffer solution containing a 50 : 50 mixture of H(2)O and (18)O-labeled H(2)O is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The advent of stable isotope labeling that utilizes 18 O-, 15 N-and 13 C-labeling as well as isotopecoded affinity tag, either by chemical derivatization or metabolic incorporation, enables MS to measure protein abundances quantitatively at intact protein and their proteolytic peptides [158][159][160][161][162][163][164][165][166]. These approaches are powerful because they measure relative abundance between unlabeled protein/peptide and its corresponding internal standard labeled with the heavy stable isotope.…”
Section: Stable Isotope Labelingmentioning
confidence: 99%
“…The advent of stable isotope labeling that utilizes 18 O-, 15 N-and 13 C-labeling as well as isotopecoded affinity tag, either by chemical derivatization or metabolic incorporation, enables MS to measure protein abundances quantitatively at intact protein and their proteolytic peptides [158][159][160][161][162][163][164][165][166]. These approaches are powerful because they measure relative abundance between unlabeled protein/peptide and its corresponding internal standard labeled with the heavy stable isotope.…”
Section: Stable Isotope Labelingmentioning
confidence: 99%
“…[7,8] The resulting mixture of 18 O-labeled RNase T1 digestion products was then incubated in H 2 16 O solutions, and the effects of enzyme, incubation temperature and pH on back-exchange were investigated. To characterize the back-exchange process, MALDI-MS analysis of the RNase T1 digestion products was conducted.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Our approach relies on the RNase-mediated incorporation of the stable isotope 18 O during enzymatic digestion of individual RNAs or mixtures of various RNAs. [8] This enzyme-mediated isotopic labeling is similar to the approach first developed by Fenselau and coworkers for the relative quantification of proteins. [9,10] They showed that the digestion of a protein using trypsin (or other serine proteases) in the presence of an 18 O-containing buffer results in the incorporation of two 18 O molecules at the C-terminus of the peptide.…”
Section: Introductionmentioning
confidence: 95%
“…The first reported isotopic labeling strategy involved using labeled water during the RNase digestion of an RNA. 75 The catalytic mechanism for RNase digestion involves the transfer of an oxygen (as a hydroxyl) from water onto the 3'-terminus of the oligonucleotide digestion product. This enzymatic incorporation of isotopic labels has been used to improve data analysis in MS/MS experiments, 75 enable the relative quantification of RNAs (modified or not) present in 2 samples, 76,77 and allowed for the comparative analysis of RNA digests (CARD) approach, 78,79 which is described further below.…”
Section: Isotopic Labeling Of Rnase Digestion Productsmentioning
confidence: 99%